The Effect of the nursing intervention program for inguinal hernia surgery patients in Fang hospital, Chiang Mai - Sriwichai, Sawitree (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2023)
This quasi-experimental research aimed to investigate the effect of complications after inguinal hernia surgery in both the control and experimental group at Fang Hospital. A simple random sampling assignment was used, resulting in a total sample size of 40 participants, with 20 participants in the control group (receiving usual nursing care) and 20 participants in the experimental group (receiving the inguinal hernia surgery care program). The measurements taken before and after the experiment. The research instruments were: 1) Case Record Form, 2) Assessment of Knowledge before and after Form, and 3) The inguinal hernia after surgery care program at Fang Hospital, Chiang Mai. The content validity index (CVI) was 1.00, and Cronbach's alpha reliability test yielded a score of 0.97. The data were analyzed using descriptive statistics and inferential statistics, such as the Chi-square test, Fisher's exact test, paired samples t-test, and independent samples t-test, with a significance level set at p < 0.05. The results showed that there were significant differences between the control and experimental groups (p < 0.05) in terms of the mean scores of the pre-test, post-test, and complications after surgery on days 0-1 and 2 weeks after surgery. However, the results were not significant on day 2 after surgery.